Penerapan Media Teka-Teki Silang Pada Pembelajaran Tematik Terhadap Minat Belajar Siswa Kelas V di SD Swasta Tiara - Ivo Ardila; Ibnatun Salis; Fransiska Mariance Nainggolan; Al Hilal Hamdi Rambe; Yusnadi Yusnadi; Anita Yus (Jurnal Tematik, 2025)
The main problem underlying this research is the low learning interest of fifth-grade students at Tiara Private Elementary School, which is evident from their lack of interest and minimal activeness in thematic learning. This research aims to comprehensively describe the content of the Crossword Puzzle media, the implementation of the Crossword Puzzle media, and the impact of its use on students' learning interest. The method used is descriptive qualitative with 30 students and their fifth-grade homeroom teachers as subjects. Data were collected through interviews, questionnaires, and documentation, then analyzed narratively. The results show that the content of the Crossword Puzzle covers Indonesian, Science, and Mathematics materials with descending and horizontal questions that are in accordance with the thematic concept. The implementation of the Crossword Puzzle was carried out interactively and in groups, accompanied by discussions and feedback. Learning interest when the Crossword Puzzle media was applied to fifth-grade students experienced a significant increase. This increase is seen from the indicators of students' attention, involvement, and interest which are in the high category, while the aspect of feelings of pleasure reached the very high category. Overall, the level of students' learning interest is in the high category. Thus, this study shows that crossword puzzle media can be an effective learning alternative to increase students' interest in learning thematic learning.